2021
DOI: 10.1093/jas/skab242
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alters bovine uterine artery hemodynamics, vaginal temperatures, and fetal morphometrics during late gestational nutrient restriction in a season-dependent manner

Abstract: The objectives were to examine melatonin mediated changes in temporal uterine blood flow (UBF), vaginal temperatures (VT), and fetal morphometrics in 54 commercial Brangus heifers (Fall, n = 29; Summer, n = 25) during compromised pregnancy. At d160 of gestation, heifers were assigned to 1 of 4 treatments consisting of adequately fed (ADQ-CON; 100% NRC; n = 13), global nutrient restricted (RES-CON; 60% NRC; n =13), and ADQ or RES supplemented with 20 mg/d of melatonin (ADQ-MEL, n = 13; RES-MEL, n = 15). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Maternal body weight results are further explained in Contreras-Correa et al [20]. Briefly, maternal body weight, fetal body weight, and fetal thoracic girth were decreased (p < 0.05) in RES-versus ADQ-fed heifers at day 240 of gestation (Table 1).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Maternal body weight results are further explained in Contreras-Correa et al [20]. Briefly, maternal body weight, fetal body weight, and fetal thoracic girth were decreased (p < 0.05) in RES-versus ADQ-fed heifers at day 240 of gestation (Table 1).…”
Section: Resultsmentioning
confidence: 74%
“…Eighty Brangus heifers were artificially inseminated using a single sire at the H. H. Leveck Animal Research Center (Starkville, MS, USA). Animal management and developmental programming results are further presented in [ 20 ]. Pregnancy was confirmed by day 35 post-insemination and only singleton bearing heifers were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin supplementation was shown to reduce core body temperature during daytime in humans; a drop of 0.30 °C was observed when supplemented with 5 mg of melatonin [ 54 ]. More recently, Contreras-Correa et al [ 42 ] reported that 20 mg/d of dietary melatonin decreased vaginal temperature in pregnant heifers during the summertime. Nevertheless, Samuel et al [ 55 ] reported no differences in rectal temperature in late gestational cows after supplementing with melatonin implants during summer.…”
Section: Circadian Rhythms Environmental Factors and Body Temperaturementioning
confidence: 99%
“…Indeed, fetal hypoxemia and hypoglycemia in heat stress-induced sheep models of placental insufficiency can exceed 50% reductions near term ( Macko et al, 2016 ; Wai et al, 2018 ; Stremming et al, 2020 ), creating a clear need for changes in metabolic processes and growth trajectories ( Lackman et al, 2001 ; Gagnon, 2003 ). The phenomenon of fetal hypoglycemia can be partially mimicked by sustained maternal undernutrition, which can decrease fetal growth despite little or no impact on the size or vascularity of the placenta ( Lemley et al, 2012 ; Eifert et al, 2015 ; Edwards et al, 2020 ; Contreras-Correa et al, 2021 ). Interestingly, diminished placental transfer of amino acids due to downsizing of system A and L transporters does not necessarily manifest in reduced fetal blood concentrations ( Pantham et al, 2016 ; Wai et al, 2018 ), as the IUGR fetus compensates by slowing its protein utilization and accretion rates ( Rozance et al, 2018 ; Wai et al, 2018 ; Stremming et al, 2020 ).…”
Section: Causes and Progression Of Iugrmentioning
confidence: 99%